2008
DOI: 10.1586/17474086.1.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Inherited predisposition to chronic lymphocytic leukemia

Abstract: Inherited susceptibility to chronic lymphocytic leukemia (CLL) has been recognized for decades. Approximately 10% of individuals with CLL report a family history of CLL or a related lymphoproliferative disorder, and genetic predisposition is the best understood risk factor for CLL. Studies of familial CLL have suggested that the disease features are largely similar to sporadic CLL, although recent data suggest that familial CLL may more commonly show somatic hypermutation of the immunoglobulin heavy-chain vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 111 publications
(98 reference statements)
1
18
0
1
Order By: Relevance
“…Asians have also significantly lower rates of CLL than Caucasian Europeans or Americans do [25]. This, coupled with the familial aggregation often observed in families with CLL, might argue in favor of a potential gene-inherited status, perhaps including UGT1A1, among others, as one of the possible shared predisposing factors to CLL of the western world [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Asians have also significantly lower rates of CLL than Caucasian Europeans or Americans do [25]. This, coupled with the familial aggregation often observed in families with CLL, might argue in favor of a potential gene-inherited status, perhaps including UGT1A1, among others, as one of the possible shared predisposing factors to CLL of the western world [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study identified linkage to 6p22, the site of the MHC locus, in familial CLL. Many early studies of specific HLA loci in relation to familial CLL have yielded conflicting results and as yet there is little clarity on the significance if any of this association [Brown, 2008]. Thus, the overall results of the largest linkage analysis performed across multiple families in CLL have unfortunately been largely inconclusive.…”
Section: Early Studies Looking For Genesmentioning
confidence: 99%
“…Moreover, these technologies are likely to be applied to studying inherited predisposition for CLL [108,109], as this disease has a high incidence of familial cases. This area of investigation might provide important clues to the interaction between existing germline mutations and acquired somatic mutagenesis.…”
Section: Discussionmentioning
confidence: 99%